2014
DOI: 10.1089/ham.2013.1086
|View full text |Cite
|
Sign up to set email alerts
|

Late Hyperbaric Oxygen Treatment of Cilioretinal Artery Occlusion With Nonischemic Central Retinal Vein Occlusion Secondary to High Altitude

Abstract: CRVO related CRAO should be regarded as a rare complication of exposure to high altitude and HBO seems to be the treatment of choice of high altitude related co-occurence of CRVO and CRAO in the late period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Intravenous fibrinolytic therapy may also induce serious haemorrhagic events, and the time of symptom onset is critical to be safe and effective [ 17 ]. In terms of oxygen therapy, the outcome remains inconsistent [ 18 20 ]. Because there are few randomized controlled trials (RCTs) and many case reports in the literature, there has been no meta-analysis on oxygen therapy in RAO patients.…”
Section: Introductionmentioning
confidence: 99%
“…Intravenous fibrinolytic therapy may also induce serious haemorrhagic events, and the time of symptom onset is critical to be safe and effective [ 17 ]. In terms of oxygen therapy, the outcome remains inconsistent [ 18 20 ]. Because there are few randomized controlled trials (RCTs) and many case reports in the literature, there has been no meta-analysis on oxygen therapy in RAO patients.…”
Section: Introductionmentioning
confidence: 99%
“…HBO has the ability to drastically increase the partial pressure of oxygen in the tissues of the body. The oxygen partial pressures achievable using HBO is much higher than those achievable while breathing pure oxygen at normobaric conditions (i.e., at normal atmospheric pressure, 0.101325 MPa) [7]. In ophthalmology HBO is beneficial for diabetic retinopathy and CRAO patients [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…A case of central retinal artery occlusion secondary to bilateral buried optic nerve drusen at high altitude was reported in 1995 [ 5 ], while another case of central retinal artery occlusion caused by the expansion of intraocular gas during mountain travel at high altitude was reported in 2002 [ 6 ]. A recent report has shown that cilioretinal artery occlusion and related central retinal vein occlusion occurred as a complication following high-altitude exposure [ 7 ]. It has been speculated that the reason for a few reports of retinal artery occlusion secondary to high-altitude exposure might be that some clinicians do not master the pathogeny of retinal vascular occlusion, thus do not inquire the patient’s travel history or consider high altitude as a risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that HBO treatment is a safe, manageable, low-cost, and effective treatment for retinal artery occlusion [ 7 ]. HBO treatment have an effect on visual outcome in patients with BRAO [ 18 ].…”
Section: Discussionmentioning
confidence: 99%